2019
DOI: 10.1055/s-0039-1683427
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Plasma Mitochondrial DNA and Cytokine Profiles of Elderly Patients Undergoing Minimally Invasive Aortic Valve Replacement

Abstract: Introduction Mitochondrial DNA (mtDNA) is gaining increasing interest as a marker of cellular damage and could also act as an inflammatory mediator in cardiopulmonary bypass induced postoperative inflammatory response. Although minimally invasive heart valve surgery reportedly reduces inflammation, the mtDNA and cytokine profile in this context remains unclear. Materials and Methods Here, we report a prospective series of 40 elderly patients with aortic stenosis who underwent bioprosthetic aortic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
1
0
2
Order By: Relevance
“…Over the past few years, the association between the level of circulating mtDNA and various pathologies has been actively studied. Thus, the authors of one study note an increase in circulating mtDNA and cytokines in plasma in all elderly patients without assessing the severity of the condition and the postoperative status after minimally invasive aortic valve replacement [ 11 ]. Another group of researchers found that patients with cardioplegic arrest had higher expression of COX III (cyclooxygenase III), NADH1 (Nicotinamide adenine dinucleotide 1), NADH2, and Cyto B (cytochrome B) genes compared to healthy participants.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, the association between the level of circulating mtDNA and various pathologies has been actively studied. Thus, the authors of one study note an increase in circulating mtDNA and cytokines in plasma in all elderly patients without assessing the severity of the condition and the postoperative status after minimally invasive aortic valve replacement [ 11 ]. Another group of researchers found that patients with cardioplegic arrest had higher expression of COX III (cyclooxygenase III), NADH1 (Nicotinamide adenine dinucleotide 1), NADH2, and Cyto B (cytochrome B) genes compared to healthy participants.…”
Section: Introductionmentioning
confidence: 99%
“…Estudo mostra que menores tempos de circulação extracorpórea e de anoxia observados com uso de prótese sem suturas foram associados com menores níveis de citocinas pro-inflamatórias no período pós-operatório (13).…”
unclassified
“…Estudo na Espanha avaliando a resposta inflamatória em pacientes submetidos a substituição valvar aórtica por cirurgia com prótese convencional vs próteses sem suturas, observaram tempos de pinçamento aórtico e de CEC menores no grupo da prótese sem sutura associada à níveis pós-operatórios significativamente mais baixos de IL-6 (13).…”
unclassified